A male-sterile mutant with necrosis-like dark spots on anthers was generated in cotton - Zhang, Jun; Wu, Peng; Li, Ning; Xu, Xiaolan; Wang, Songxin; Chang, Siyuan; Zhang, Yuping; Wang, Xingxing; Liu, Wangshu; Ma, Yizan; Manghwar, Hakim; Zhang, Xianlong; et al. (Frontiers in Plant Science, 2023)
Although conventional hybrid breeding has paved the way for improving cotton production and other properties, it is undoubtedly time and labor consuming, while the cultivation of male sterile line can fix the problem. Here, we induced male sterile mutants by simultaneously editing three cotton EXCESS MICROSPOROCYTES1 (GhEMS1) genes by CRISPR/Cas9. Notably, the GhEMS1 genes are homologous to AtEMS1 genes, which inhibit the production of middle layer and tapetum cells as well, leading to male sterility in cotton. Interestingly, there are necrosis-like dark spots on the surface of the anthers of GhEMS1s mutants, which is different from AtEMS1 mutant whose anther surface is clean and smooth, suggesting that the function of EMS1 gene has not been uncovered yet. Moreover, we have detected mutations in GhEMS1 genes from T0 to T3 mutant plants, which had necrosis-like dark spots as well, indicating that the mutation of the three GhEMS1 genes could be stably inherited. Dynamic transcriptomes showed plant hormone pathway and anther development genetic network were differential expression in mutant and wild-type anthers. And the lower level of IAA content in the mutant anthers than that in the wild type at four anther developmental stages may be the reason for the male sterility. This study not only facilitates the exploration of the basic research of cotton male sterile lines, but also provides germplasms for accelerating the hybrid breeding in cotton.